Tax information: some aspects of the right of access - Мандзюк, Олег Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article analyses national legal regulation of the public relations in the field of tax information. The author investigates compliance of tax legislation with the Law of Ukraine «On access to public information» in the context of the mechanism of access to tax information, directions of providing publicity of the tax information by tax authorities, procedures of protection of the rights of access to information.